Who Knocks on the Door of Portfolio Performance Heaven: Sinner or Saint Investors? - José Luis Miralles-Quirós; María Mar Miralles-Quirós (Mathematics, 2020)
To sin, or not to sin: that has been the question for many people for a long time, and nowadays that question has moved to the financial markets. The existence of studies that show that investing in vice sectors such as the alcohol, tobacco, and gambling industries, collectively known as the “triumvirate of Sin”, is profitable has created some uncertainty for investors who wonder whether or not to be socially responsible. We show that by implementing an investment strategy based on the Fama–French five-factor model, “saint” investors obtain better portfolio performance, even when transaction costs are taken into consideration, and therefore they are the ones chosen to knock on the door of portfolio performance heaven.